2008
DOI: 10.1017/s0033822200053509
|View full text |Cite
|
Sign up to set email alerts
|

New Marine ΔR Values for the South Pacific Subtropical Gyre Region

Abstract: ABSTRACT. This paper presents 31 new ΔR results of known-age, pre-AD 1950 shells from the South Pacific subtropical gyre region, spanning from the Tuamotu Archipelago in the east to New Caledonia in the west. This doubles the number of available ΔR values for the Oceania region. These values indicate that the regional offset (ΔR) from the modeled radiocarbon marine age has remained relatively constant over the last 100 yr prior to 1950. Variation from the norm can be attributed to various influences including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 79 publications
(101 reference statements)
5
70
0
Order By: Relevance
“…tend to have slightly depleted 14 C signatures indicative of high intertidal habitats influenced by hardwaters, while 14 C and 13 C values for Anadara granosa are influenced by the ingestion of enriched terrestrial carbon sources in keeping with this species' preference for sandy mud bordering the mangrove swamp. Anadara antiquata and echinoids have isotope values closer to the global marine average (AR ~ 0) and comparable to that calculated by Petchey et al (2008a) and Ulm (2006) for pre-AD 1950 shellfish collected in the region (Figure 1). …”
Section: Settingsupporting
confidence: 75%
“…tend to have slightly depleted 14 C signatures indicative of high intertidal habitats influenced by hardwaters, while 14 C and 13 C values for Anadara granosa are influenced by the ingestion of enriched terrestrial carbon sources in keeping with this species' preference for sandy mud bordering the mangrove swamp. Anadara antiquata and echinoids have isotope values closer to the global marine average (AR ~ 0) and comparable to that calculated by Petchey et al (2008a) and Ulm (2006) for pre-AD 1950 shellfish collected in the region (Figure 1). …”
Section: Settingsupporting
confidence: 75%
“…Unusually low R have been measured on archaeological shells from Mussau (-293 ± 92 14 C yr), located just outside of the Bismarck Sea. This range of variation within a relatively small area means it is impractical to apply a regional R value as has been possible for the central South Pacific Gyre region (R = 5.5 ± 21 14 C yr) (Petchey et al 2008; Table 1). Although we recognize that this region is highly complex and the variability present is large, we argue that, when local oceanographic conditions are taken into consideration, it is possible to apply valid and statistically sound subregional R values that incorporate the variation observed.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has indicated that considerable R variation is possible not just in estuarine or lagoon environments where terrestrial 14 C input is likely (Ulm et al 2009;Petchey and Clark 2011), but also where ocean currents meet continental landmasses, opposing currents, or island chains (Petchey et al 2008). The Bismarck Sea has previously been identified as problematic in this respect (Petchey et al 2004(Petchey et al , 2005McGregor et al 2008).…”
Section: F Petchey and S Ulmmentioning
confidence: 99%
“…Class 1 dates give the greatest chance of establishing an accurate age for recent colonization events. The remaining dates were placed into Class 2, as they are associated with unacceptably low levels of precision and/or accuracy for the task of defining relatively short colonization chronologies (i.e., samples with known or potential inbuilt age (including unidentified charcoal) (7); marine reservoir effect (33,34); dietary, postdepositional or pretreatment contamination of bone (35)(36)(37); and imprecision associated with marine calibration (5,38). Although many dates from unidentified charcoal and marine shell offer results consistent with Class 1 dates from the same contexts (15), their reliability cannot be established to the same extent.…”
Section: Methodsmentioning
confidence: 99%